(untitled) (Conference on English Language Teaching, 2025)
This paper explores a comprehensive theoretical analysis of the interrelation of anxiety and motivation in second language learning processes. The researcher proposes the Affective-Cognitive Mediation Framework (ACMF) and offers an explanation of the previously disjointed concepts by arguing that both anxiety and motivation function as processes within a system that operates over multiple time scales rather than a singular, fixed, and defined entity. Drawing from Dynamic Systems Theory, sociocultural theory, and some branches of educational psychology, our framework reveals four primary mediating mechanisms: attention control, identity change, emotion evaluation, and social identification. Unlike traditional models that treat anxiety fundamentally as an inertial element of motivation, the ACMF describes certain anxiety forms that may, under specific conditions, serve as catalysts for motivational redirection. This approach provides an explanation for the contradictory evidence across the literature and forecast outcomes such as differences in individual responses to challenges in language learning based on their emotions. The researcher argues further that this framework explains the lack of productivity in many studies by providing hypotheses about the value of well-defined interventions and changes in the theory guiding pedagogy. Moreover, this study contributes to the existing literature by providing a clear conceptual framework that integrates what is already known and offers novel insights into the emotional aspects of second language acquisition.